Mental health and social support perceived in fourth grade schools of secondary public Educational Institutions of Lima Metropolitana - Huerta Rosales, Rosa E. (2020)
The objective of the study was to analyze the relationship between behavior problems with perceived social support, in a sample of 627 secondary school students from public Educational Institutions, to whom a data sheet, the Inventory of Behavioral Problems and the Multidimensional scale of perceived social support. The results establish that there is a significant and inverse relationship between problem behaviors with perceived social support. When there is a lower level of social support, male schoolchildren show greater problem behaviors of an anxious type and relationship; and women social and relationship problems. In the outsourcing dimension, there is a predominance of behavioral difficulties; in internalization it is somatization that reaches the highest percentage. The majority of those evaluated perceive total social support at the medium level. There are significant differences in problem behaviors, it is women who present these difficulties and greater difference in means in contrast to men; they perceive greater social support from the family compared to women who perceive greater social support from friends. The support of family and friends are relevant as a protective factor for mental health in adolescents.